Effects of informational constraints in the motor learning on the flute - J. Granda; J. C. Barbero; M. Lozano (Asociación Española de Ciencias del Deporte, 2010)
The present work gathers a study made with students of the second cycle of that (3º) that it had by objective to know the effect that produces a program of learning of the instrumental technique of flute of characterized tip to include visual and/or auditory informational limitations during the musical learning of musical pieces, conducive to improve the interpretative quality levels by means of a diminution of nº of errors during the reproduction of a musical sequence. The learning program I am carried out throughout 3 months (16 sessions), with inclusion of informational restrictions like key for the improvement of the implied motor combat operations control (coordination interdigits), participating four groups of students (a group control who learned without restrictions, an experimental group that learned with visual restrictions, an experimental group that learned with auditory restrictions and an experimental group that learned with visual and auditory restrictions). Results found not show differences significant in performance, although if a manifest tendency you relate to a diminution in nº of errors of the groups that received informational restrictions, specially those groups whom they had limited his auditory perception during certain moments of practice. Key words: Informational constraints, motor control, interdigit coordination, motor learning in music performance